MAKSIMALISASI PENDAPATAN PETANI KELAPA SAWIT DI DESA BATU BETUMPANG KECAMATAN PULAU BESAR KABUPATEN BANGKA SELATAN - Iwan - Setiawan; Eddy Jajang Jaya Atmaja (Journal of Integrated Agribusiness, 2023)
Smallholder oil palm plantations have not been able to meet the maximum level of income for their farmers. This study aims to determine the characteristics of farmers and to find out how farmers can maximize their income from their oil palm plantations. This study used a survey method, involving 43 farmers. The data is processed and analyzed using the approach to the relationship between costs and production results in order to obtain a total cost equation. From this equation, the marginal cost and average cost equations are then used to calculate the farmer's maximum income. The results showed that the more family members, the more oil palm yields that could be obtained, although most of the family members of these farmers still had low education. The income earned by oil palm farmers varies according to the area and age of their oil palm plantations. Oil palm that is getting older tends to provide less income for farmers. Oil palm farmers who have an average land area of ​​2.75 Ha and receive a selling price of IDR 1,456.00/Kg Fresh Fruit Bunches (FFB) only earn IDR 788,531.00/Ha. At the same FFB price level, farmers can get a maximum income of IDR 1,081,093.00/Ha, by selling 1,334 Kg of FFB. If for example the price of FFB is IDR 700.00/Kg, farmers can also get a maximum income of IDR 169,562.00/Ha by selling 2,550 Kg of FFB. Basically, farmers can obtain maximum income by adjusting the amount of FFB sold based on the prevailing FFB price level. This can only be done if the farmer uses the maximum income calculation formula as has been obtained from the research results.